Comparison of Topical and Combined Treatment of Bacterial Vaginosis - Naila Khawer, Sadaf Kashif, Amna Asif, Shagufta Jabbar, Zille Huma, Fariha Arshad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare efficacy of topical clindamycin versus combined effect of metronidazole and clindamycin in bacterial vaginosis patients. Study Type: Randomized controlled trial Place and Duration of Study: Obstetrics and Gynecology Unit 3, Services hospital, Lahore from 25th January 2018 to 25th July 2018. Methodology: Sixty patients fulfilled selection criteria were divided randomly in twp study groups. Clindamycin topical application was given to group A and second group was given clindamycin topical treatment plus oral metronidazole. Patients were called in OPD after 2 days and checked for bacterial vaginosis. Results: The mean age was 30.35±7.65 years. Twelve (20%) females were nulliparous, 16 (26.7%) had parity 1, 16 (26.7%) had parity 2, 10 (16.7%) had parity 3 and 6 (10%) had parity 4. In clindamycin group, efficacy was achieved in 22 (73.3%) cases while 28 (93.3%) cases in combination group. The difference between both groups was significant (p<0.05). Conclusion: The combination of clindamycin and metronidazole is more effective in resolution of bacterial vaginosis than clindamycin alone.